Experimental investigations of process parameters on mechanical properties for PLA during processing in FDM. (30th September 2022) - Chokshi, Harsh; Shah, Dhaval B.; Patel, Kaushik M.; Joshi, Shashikant J.
ABSTRACT: One of the additive manufacturing techniques known as fused deposition modelling (FDM) has been proven to be the best alternative for fabricating complex geometry from Polylactic acid (PLA). The mechanical properties of the printed parts of PLA material by the FDM technique mainly depend on the process parameters. This study investigates the effects of three crucial FDM parameters, that is, layer thickness, infill geometry and the number of perimeter on the mechanical properties of PLA material. The tensile strength and flexural strength have been measured for fabricated PLA samples using FDM as per ASTM standards. The mean effect and interaction effects of each process parameter on the tensile strength and flexural strength have been studied. It has been found that infill geometry and the number of perimeters have a significant influence on the tensile strength whereas layer height and the number of perimeters have a significant influence on the flexural strength. The specimens printed at 0.100 mm layer height, gyroid-type infill geometry and 6 number of perimeter have maximum tensile strength whereas the specimen printed at 0.150 mm layer height, concentric infill geometry and 4 number of perimeter have maximum flexural strength.